Mycoplasma hominis Detection in Females Suffering from Vaginitis Who Are Using a Contraceptive Device - Muhannad Abdullah Khalaf; Mustafa Mahir Khudur (Zien Journals, 2022)
This hospital based study was done in Kirkuk city from June to November 2021 In our study, it was aimed to investigate the frequency of M.hominis in women who use an intrauterine contraceptive device, and to compare that incidence with the incidence of Mycoplasma hominis in women who use other forms of contraception. Deep endocervical swabs were collected from 100 fertile women who attended the gynecology unit in Gynecological and Pediatric Hospital in Kirkuk city (50 of them using IUCD (cases) and 50 using other methods of contraception as barrier or hormonal as control group). For each patient three cervicovaginal samples were taken by swabs for microbiological study. The following items were included in the collection of vaginal swabs:Only a portion of the swab package had been opened. Two- The swab was gently rotated for 10 to 30 seconds after it had been carefully inserted into the vagina about two inches (5 cm) past the introitus. As soon as the swab touched the vaginal walls and moisture, it was drawn away from the skin without making contact with the skin. In accordance with standard operating procedures, the colonies that had grown on the media were harvested, purified, and identified. Smears were prepared from bacterial colonies, stained with Gram stain, and examined under a light microscope for morphological characteristics. The study revealed that 80 percent of women who have used IUCD (cases) have a positive deep cervical swab for culture, compared to 24 percent of women who have used other types of contraception such as barrier or hormonal contraception (control group). Mycoplasma hominis (52.5 percent) was the most frequently isolated bacteria from women who had used IUCD. Ureoplasma ureoliticum and E. coli were the most frequently isolated bacteria from the control group, with 33.33 percent for each and no Mycoplasma hominis isolated from control women. According to the findings of the study, 50 percent of women who used IUCD with positive culture suffered from Pelvic pain, 37.5 percent suffered from abnormal vaginal discharge, 40 percent suffered from burning, 15 percent suffered from fever, 25 percent suffered from vaginal dyspareunia and vaginal itching, and 5 percent suffered from no symptoms. The study showed that majority of women used IUCD who infected with M. hominis were used IUCD for more than 6 years (38.1%) and 9.52% in women who used IUCD less than 1 year, while 40% of women without infection were within group below 1 year.
Keywords: Mycoplama; contraceptive devices; Vaginitis